On the Design and Effectiveness of Targeted Expenditure Programs - Ahmad, Ehtisham; Martinez, Leonardo (Washington, D.C. : International Monetary Fund, 2004)
This paper argues that both horizontal and intertemporal competition among recipient governments are needed in order to ensure incentives for effective utilization of targeted transfers. This has implications for budgeting frameworks and the types of information needed that might be amenable to formal contracting between the levels of government.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Central Government; Fund; Local Government; Program; WP